Health and Body Mass Index: No Simple Relationship - Olaf Hübler (Institute of Labor Economics (IZA), 2017)
Many studies have shown that obesity is a serious health problem for our society. Empirical analyses often neglect a number of methodological issues and relevant influences on health. This paper investigates empirically whether neglecting these items leads to systematically different estimates. Based on data from the German Socio-Economic Panel, this study derives the following results. (1) Many combinations of weight and height lead to the same health status. (2) Obese people have a significantly worse state of health. (3) The hypothesis has to be rejected that weight is an exogenous influence on health. (4) High income helps to improve men's health while deviations between desired and actual working hours induce negative effects. (5) The more siblings a woman has and the lower her father's social status, the worse is her health status. (6) Smoking is not good for health, a well-known fact. Especially for underweight individuals we detect the negative influence on health. Women are less affected. (7) A healthy diet strengthens the resilience for individuals who are not obese. (8) Long but not too long sleeping hours and sporting activities during youth contribute to a good health status. (9) Weight fluctuations induce negative effects on the health of women only. (10) Four of the big five components of personality, namely openness, extraversion, conscientiousness and agreeableness, contribute to resilience against health problems for underweight people.
Keywords: D03; I12; J16; J24; J81; 330; health; body mass index; underweight; obesity; gender; resilience; vulnerability